UJI PERFORMA BIODISEL DARI MINYAK JARAK PAGAR YANG DIPRODUKSI SECARA ENZIMATIS PADA MESIN DISEL - Kurdi, Ojo (ROTASI, 2006)
Jatropha curcas oil is one of potential plants for hydrocarbon resource or energy resource in Indonesia. Whereas the oil cannot be used directly because of its high viscosity, low cetane number, presence of free fatty acid, low volitile, presence of gum and there will be high deposit if it is used as a direct fuel (Fangrui Ma, 1999). Therefore, it must be convert to a form of alkyl ester or in famous term of biodiesel. Biodiesel produkction from jatropha curcus is basically methanolysis reaction, the reaction between triglyceride and methanol that yields fatty acid metyl ester and glycerol. This reaction can be performed chemically by using catalyst and enzymatic. Pre-study has been done in laboratory scale by using jatropha oil in enzimatic reactor. The result shows that methanolysis reaction of triglyceride using biocatalyst is very potential to produce biodiesel (Yulianto, M.E., dkk., 2005). Biodiesel application to diesel engine has widely been investigated. Several studies noted that biodiesel can be used to diesel engine for long time. Biodiesel is used by mixing with petro-diesel. The mixing has a range from 2/98% (B2) to 100% (B100). There are some studies namely output energy, lubrication condition, and gas emission. This research was conducted to study output energy or engine brake power fuelling with biodiesel-petro diesel compared with fuelling with petro diesel and fuel efficiency that calculated from fuel consumption per unit power. The research was begun with literature study about diesel engine theory, biodiesel, and biodiesel application to diesel engine. Laboratory experiments were done trhough some steps : properties test, petro diesel engine test , B10 engine test, data analyzing and conclusion. Diesel engine used in this test has power of 8.5 kW which was coupled to 5 kW generator at 1500 rpm. Applied variable loads were lamps whereas shaft speed was measured by using stroboscope. Fuel consumption was measured by weighing fuel that had been used. The result shows that brake power of engine fuelling with B10 is 4.5% lower than that fuelling with petro-diesel. Whereas the efficiency is 1.7 % higher